Rubber plantations and carbon management - Nath, Arun Jyoti; Brahma, Biplab; Das, Ashesh Kumar (Oakville, ON, Canada ; Palm Bay, Florida : Apple Academic Press, 2019)
"With the increasing atmospheric carbon dioxide concentration and the resulting environmental consequences for plants, it is necessary to consider the future of rubber plantations, an important source of latex for rubber production. In Rubber Plantations and Carbon Management, the authors explore the ecology of rubber plantations in the context of carbon management under a scenario of our changing climate. The authors provide an in-depth study of the carbon stock and sequestration potentiality of rubber plantations. The volume also provides information on a biomass estimating model that can be used in future study of non-harvesting biomass estimation for a variety of plants. Topics in the volume address ecosystem biomass carbon losses through clear felling management systems, ecosystem carbon sequestration, and fine root dynamics in carbon balance under a rubber plantation management system. The volume concludes with an examination of future strategies and determines that rubber plantation development by replacing natural forests should not be encouraged, though progressive land use changes, for example, conversion of degraded forest lands or grasslands to rubber plantations, can enhance biomass and soil stock. The expansion of rubber tree plantations with best management practices in degraded forest, grasslands, or fallow lands can offer an ecological stability with significant socioeconomical support. This volume is the first of its kind on this important topic. The volume will be valuable for faculty and students, cultivators, researchers, rubber board officials, and many others. It will also aid in policy formulation at the scientific community level for those who are working on climate change adaptation and mitigation aspects"--
Cover; Half Title; Title Page; Copyright Page; About the Authors; Table of Contents; Abbreviations; Preface; 1: General Introduction; 2: Biomass Models and Biomass Carbon Stocks; 3: Potential Loss of Biomass Carbon; 4: Impact of Land Use Changes on Soil Organic Carbon; 5: Ecosystem Carbon Sequestration; 6: Soil Carbon Sequestration; 7: Fine Root Dynamics and Carbon Management; 8: Conclusions and Recommendations; Index
OCLC-licensed vendor bibliographic record.
Keywords: Rubber plantations -- Environmental aspects; Carbon dioxide -- Environmental aspects; Carbon dioxide mitigation; SCIENCE / General; TECHNOLOGY / Agriculture / Forestry